Public relations via Twitter : an analysis of South African commercial organisations - Moyo, Lungile (Centre for Film and Media Studies, 2015)
Background: As more people are using mobile phones to receive and read news, Twitter has become a popular communication tool, particularly for commercial brands in South Africa. This thesis investigates twelve South African organisations’ use of Twitter. It portrays Twitter as an informational network that allows conversational communication. It seeks to identify how commercial brands in South Africa use Twitter as a public relations/communication tool. Aim and Objective: In attempt to learn whether current South African tweets among certain organisations follow Western practices of public relations, the study aims to understand and identify how commercial brands in South Africa communicate with their publics through Twitter. Revealing the content of these organisations’ tweets facilitated the fulfilment of this objective.